PKMS Kelompok Konveksi Rumahan dalam Upaya Peningkatan Pendapatan Rumah Tangga di Desa Jolotundo Kecamatan Lasem, Kabupaten Rembang - Siti Alliyah (Universitas Islam Nahdlatul Ulama Jepara, 2020)
The PKMS program was carried out in Jolotundo Village, Lasem District, Rembang Regency with Kenanga Sewing Group partners. Jolotundo village is famous for its citizens, especially women who open home-made convection. By seeing the business potential which is still very broad and the convection business is one of the leading sectors of Jolotundo Village, then home-based convection should have priority so that it can develop as one of the sectors that will increase people's income. The purpose of this program is to increase the income of the Kenanga Convection Group. The methodology used is counseling, management and entrepreneurship training and e-commerce practices. The results of the PKMS program include: 1) the partner group is able to create an online shop (Tokopedia) and a blog 2) the partner group is able to make good and orderly financial accounting 3) the partner group starts to dare to make products without relying on orders, 4) the partner group products have used packaging with complete hangtags and brands on the product